An Alternative Model of Project-Based Assessment of Writing Competence in Junior High School - Maria Wulandari (Indonesian Journal of English Language Studies (IJELS), 2015)
To improve the quality of education outcomes, English teachers have to enhance their competence in assessing students learning. In fact, in Curriculum 2013, many Englishteachers find difficulties in assessing students learning. One of the reasons is lack ofknowledge about the model of assessment for Curriculum 2013. Therefore, in this article, analternative model of project-based assessment is proposed. The focus here is on the Englishwriting competence. This article actually concerns with a proposed model of assessment withpilot study data. The pilot study was conducted by adapting research and development (R D) procedure. The participants of the study were English teachers from Yogyakarta andgraduate students of English Language Studies, Sanata Dharma University. The techniqueused were questionnaire and Focus Group Discussion (FGD). The data were verbal andnumerical. The result of the pilot study shows that the model is good but needs someimprovement. It also reveals some principles in developing the effective project-basedassessment model: practical, holistic, systematic, systemic, relevant, authentic, andmeaningful. In addition, the project-based instrument should have: clear objectives, clearscoring criteria, clear instruction, clear items and feedback.Keywords: alternative model, project-based assessment, writing competence